Social Interactions and Cultural Repertoires as Resources for Coping With Breast Cancer. (February 2017) - Zucchermaglio, Cristina; Alby, Francesca
The article aims to better understand the role of cultural and social resources for coping with cancer as a disruptive experience. Fourteen women who had recently received a diagnosis of breast cancer and started a treatment in an Italian hospital have been interviewed individually to elicit narratives regarding the interactions with the other patients. The analysis focused on the role played by social interactions and cultural repertoires as devices for making sense of and facing the illness. Results show that patients use both interactive as well as noninteractive strategies. In both cases, however, the other patients are an important reference in the interviewees' accounts. Even for noninteracting patients, the others and specific groups are taken into account and displayed in their narratives either directly or indirectly (i.e., typified or imagined), contributing to interpret and address what they experienced as cancer patients. Moreover, results provide empirical evidence of the various cultural repertoires (including examples retraceable to popular culture) on which people rely to address and cope with the illness. These results widen the individualistic framework commonly used in the understanding of coping strategies by including psychosocial phenomena that are created outside the individual in the complex interactions with the social and cultural world.